Qualification Of Human Resources To Apply Electronic Management A case study In The Ministry Of Science And Technology - عبد الزيدي ناظم جواد; خليل زينب مصطفى (Journal of Economics and Administrative Sciences, 2015)
This research aims to shed light on the reality of the process of rehabilitation of human resources for the implementation of electronic management practice in the ministry, and availability requirements of the application of electronic management and diagnosis of the most important stages and steps that can be followed in the process of transition towards electronic management to keep abreast of developments in the field of information technology, has been the application of this research in the Ministry of science and technology on a group of heads of departments and directors of the people in the departments of the Ministry through the use of case study method, which includes cohabitation field interviews and gather information by asking questions to officials and employees in the departments of the Ministry, and access to official documents and records and take advantage of them, and used the checklist as a key tool been reliable in gathering information which was divided into two main axis ensures electronic management and the requirements of their application (support of senior management, financial resources, technical resources, administrative organization, knowledge and information) The main axis of the second guarantees the questions about the qualification of human resources and tactics (education, training, empowerment, job descriptions and practical experience, administrative development) and through data collection and analysis was reached a set of conclusions and recommendations which were the most important that the ministry is available has applied the requirements of electronic management well but suffered weakness with respect to tactics used for the rehabilitation of human resources for the implementation of electronic administration. The ministry continued interest in providing electronic management requirements with greater attention to the rehabilitation of human resources and that the importance of this subject at the present time.